Ultrasonic velocity and isentropic compressibility of binary fluid mixtures at 298.15 K - Rajeev Kumar Shukla; S. N. Dixit; Pratima Jain; Preeti Mishra; Sweta Sharma (Orbital: The Electronic Journal of Chemistry, 2011)
Speed of sound and isentropic compressibility of six polar-nonpolar cyclic liquid binary mixtures has been computed over the whole composition range at 298.15 K with the help of Prigogine-Flory-Patterson theory. Experimental surface tension and experimental density data were utilized in the prediction of sound velocity with the use of Auerbach relation. A comparison has then been carried out as regards the merit and demerits of the employed relations. An attempt has also been made to study the nature and magnitude of molecular interactions involved in the liquid mixture.